Sustainability of Traditional Markets on Face of Modern Market in Province of Bangka Belitung Islands - Gani, Azza Faulin; Wardhani, Rulyanti Susi; Yunita, Anggraeni; Zukhri, Nizwan (Journal of Community Service and Society Empowerment, 2025)
Traditional markets in the Bangka Belitung Province play a significant role in supporting the local economy, particularly for Micro, Small, and Medium Enterprises (MSMEs). However, the emergence of modern markets, which offer convenience, efficiency, and a wider variety of products, presents a major challenge to the sustainability of traditional markets. This study aims to assess the sustainability of traditional markets in Bangka Belitung in the face of competition from modern markets. The methods used include field observations, interviews with traders and market managers, and consumer surveys. The results indicate that the revitalization of traditional markets through infrastructure improvements and digitalization training has enhanced competitiveness. There has been a 15% increase in visitor numbers, and traders who participated in digital training saw an average income increase of 10%. Additionally, 65% of traders have adopted digital payment systems. However, some traders still face difficulties in adopting new technology. Consumer satisfaction has increased from 60% to 78% after revitalization efforts. Collaboration between the government, academics, and the community is a crucial factor in supporting the sustainability of traditional markets amid competition from modern markets.